Using wood on King Island, Alaska - Alix, Claire (Études/Inuit/Studies, 2012)
AbstractUgiuvak, or King Island, off the coast of the Seward Peninsula in the Bering Strait, is among the few Arctic villages with stilt houses in an environment where wood is essentially lacking. In 1899, Edward W. Nelson, describing the island’s architecture, noted that wood was abundant. Today, the contrast is striking between the bareness and steepness of the coast and the extensive use of wood in the village. This article presents information about wood procurement and use as building material on Ugiuvak in the last 300 years based on literature review, on-site observations, and discussions with members of the King Island community. It briefly reviews the origin, circulation, and deposition of driftwood in the Bering Strait region. It then explores the possibility of a relationship in the 19th century between an increase in driftwood availability and the development of stilt architecture on the island, taking into account other wood sources that became available at the time. The last 150 years of occupation of the village were marked by a transition from a solely driftwood-based economy to one where driftwood was first supplemented and then largely replaced by lumber.